A study on undernutrition and its socioeconomic correlates among toddlers in a rural area of Uttarakhand, India - Vyas, Shaili; Kandpal, S. D.; Semwal, Jayanti; ., Deepshikha (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevention of malnutrition is crucial for improving human resources. Child malnutrition is the major public health issue in many developing countries such as India. Despite global efforts for improving nutritional status of children, desired outcomes could not be achieved. Methodology The study was carried out in the villages under RHTC, field practice area of department of community Medicine, Dehradun. A sample of 500 mothers with children in the age group of 0-36 months living in the registered population of RHTC were included, where socio demographic profile were recorded. Results: Factors as Religion, family size and type parental education, father’s occupation emerged as significant predictors of under nutrition. Conclusion: The findings confirm the association of sociodemographic factors with malnutrition of their children.